2022
DOI: 10.1186/s12957-022-02555-9
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of overall survival based upon a new ferroptosis-related gene signature in patients with clear cell renal cell carcinoma

Abstract: Background Clear cell renal cell carcinoma (ccRCC) is the most common and lethal renal cell carcinoma (RCC) histological subtype. Ferroptosis is a newly discovered programmed cell death and serves an essential role in tumor occurrence and development. The purpose of this study is to analyze ferroptosis-related gene (FRG) expression profiles and to construct a multi-gene signature for predicting the prognosis of ccRCC patients. Methods RNA-sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…When paired with other clinical factors, univariate and multivariate Cox regression analysis were performed to determine whether risk score was an independent predictive factor in COAD patients (32).…”
Section: Independent Prognostic Value Assessment Of the Prognostic Modelmentioning
confidence: 99%
“…When paired with other clinical factors, univariate and multivariate Cox regression analysis were performed to determine whether risk score was an independent predictive factor in COAD patients (32).…”
Section: Independent Prognostic Value Assessment Of the Prognostic Modelmentioning
confidence: 99%
“…), or did not thoroughly established potentially significant treatments that could be used to treat the different risk groups of patients their model could stratify. For instance, Tang et al established a prognostic model on 9 autophagy-related long non-coding RNA 42 , Xu et al constructed a panel of 10 cuproptosis-associated lncRNAs 43 , Ming et al designed a panel comprising 12 N7-Methylguanosine (m7G)-related long non-coding RNAs (lncRNAs) 44 , Sun et al constructed a ferroptosis-related prognostic signature based on 19 ferroptosis-related genes 45 , Liu et al identified a 13-gene risk signature related to ccRCC patients' metabolism 46 , Zhao et al described their finding on 3 metabolic genes that were used to build a risk score model 47 , and Peng et al proposed a 3-gene methylation signature that could be used as a risk stratification tool to predict patient's outcomes and treatment response 48 . Compared these previous literature, to our existing knowledge, this is the first study to thoroughly investigate a panel of 13 proteins in ccRCC based on which we established an algorithm able to differentiate high-risk from low-risk patients, predict their 1-, 3- and 5-year OS, perform immune-related functional analysis to investigate the potential effect of immunotherapeutics in these 2 groups of patients and screen for potential drugs that could have be effective in the high and low-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging research suggested that cuproptosis and ferroptosis were key factors of KIRC development. To date, based on cuproptosis and ferroptosis, multiple biomarkers with fair prediction performance for predicting prognostic mRNA or lncRNA value in KIRC have been established [ 26 , 31 33 ]. However, the association of CRFGs and prognosis of KIRC needs to be investigated, as developing a CRFGs signature for predicting KIRC prognosis and optimizing therapeutic methods is speculated to be helpful.…”
Section: Discussionmentioning
confidence: 99%